Analytic methods in geomechanics - Chau, Kam-tim. (Boca Raton, FL : CRC Press, 2013)
'Bringing together a range of areas including tensor analysis, elasticity, plasticity, fracture mechanics and viscoelasticity, among others, this book is an indispensible guide to the fundamentals of geomechanics. It provides explanations of each subject area, using a step-by-step process with numerous worked examples. The more advanced material, such as 2-D elasticity and application of J-integral to model slipping slopes then supplies a gateway into understanding the latest research results and applying them to practical problems. The book is suitable for undergraduate and graduate students as well as professionals and researchers'--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Soil mechanics; Rock mechanics